CONTROL OF THE ADHESION QUALITY OF NIRESIST INSERTION IN CASTINGS OF DIESEL ENGINES FORCER - A. L. Majorov; N. N. Gilj (Литьë и металлургия)
The results of researches of an ultrasonic quality testing of pistons of diesel engines in casting are submitted. It is shown, that special focusing transducers should carry out for the testing. Accuracy of the testing is not worse than 0,5 % from the area of niresist insert.